2019
DOI: 10.1016/j.ebiom.2019.01.035
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA EPB41L4A-AS1 regulates glycolysis and glutaminolysis by mediating nucleolar translocation of HDAC2

Abstract: Background LncRNAs have been found to be involved in various aspects of biological processes. In this study, we aimed to uncover the molecular mechanisms of lncRNA EPB41L4A-AS1 in regulating glycolysis and glutaminolysis in cancer cells. Methods The expression of EPB41L4A-AS1 in cancer patients was analyzed in TCGA and GEO datasets. The level of cellular metabolism was determined by extracellular flux analyzer. The relationship between p53 and EPB41L4A-AS1 was explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 56 publications
2
121
0
Order By: Relevance
“…Knockdown of TIGA1 promotes microtubule depolymerization via reduced acetylated α-tubulin, which induces cellular stress and ROS production due to VDAC block by binding with free tubulin. Consequently, p38 is phosphorylated and subsequently increases HIF-1α level [101].…”
Section: Lncrnas Regulate Glutamine Metabolismmentioning
confidence: 99%
“…Knockdown of TIGA1 promotes microtubule depolymerization via reduced acetylated α-tubulin, which induces cellular stress and ROS production due to VDAC block by binding with free tubulin. Consequently, p38 is phosphorylated and subsequently increases HIF-1α level [101].…”
Section: Lncrnas Regulate Glutamine Metabolismmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs), a set of non-coding RNAs (ncRNAs) with a length of more than 200 nucleotides, make a significant contribution in cancer biology and serve as biomarkers and therapeutic targets for many human neoplastic diseases [6][7][8]. In recent years, the aberrant expression of lncRNAs has been discovered in various types of tumours, acting as oncogenes or tumour suppressors [9][10][11]. Two molecular mechanisms of lncRNAs in the development of glioma have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, reactive oxygen species were augmented, inducing the transcriptional activation of P-eIF2α/ATF4; as a consequence, the overexpression of the SNAT5 (SN2) transporter was induced, leading to an increase in glutamine consumption. Moreover, it was also demonstrated that the absence of EPB41L4A-AS1 upregulates glutaminolysis-related members such as ASCT2, GLS, ME1 and ME2 [126] (Figure 3). catabolism, which depends on GLS, although the implicated mechanisms remain unknown [127] ( Figure 3).…”
Section: Lncrna Epb41l4a-as1mentioning
confidence: 94%